Perceptions and attitudes of the use of mobile phones in English language learning - Amira Nasrin Zulfakar; Noraza Ahmad Zabidi (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2020)
Mobile Learning promotes learning strategies for 21st century as it is a human-centered approach which is a critical facet in the learning process. It generates opportunities to make meaning, build collaborative teams in a learning environment in tune with the demands of the ICT era of today. As a result, there is keen and wide interest towards Mobile Learning in many fields particularly, in education. The theoretical support for the use of mobile in learning includes the constructivist approach to learning. This paper provides a critical discussion on the attitudes and perceptions of the use of Mobile phones in learning and suggestions for language learning improvements to meet needs of current and future students.